ICT in Agriculture India and way forward - Varshney, Himanshu; Singh, S K (Indian Farming, 2019)
The ICT initiatives include development of ICT infrastructure for agricultural content and services delivery, capacity building in ICT for adapting or response to the fast changing requirements of research, technology development and knowledge dissemination in the scenario of globalized agriculture. The aim of various ICT initiatives has been mainly to create a conducive environment that could ensure better flow of knowledge, collaborations, experimentations and implementation of innovations in terms of information, communication and dissemination systems, advanced learning and state-of-the-art capacity building initiatives, value added market intelligence services, ERP based advanced planning and management systems, e-education, e-extension, online examination system, automation in agriculture, ICT enabled research platforms etc. The activities are focussed towards creation of an enabling environment for the agriculture ecosystem in the country.